2005
DOI: 10.1039/b503425f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced relaxation of nanoparticle-bound supercoiled DNA in X-ray radiation

Abstract: A therapeutic methodology was developed based on the large X-ray absorption cross-section of gold nanoparticles at high photon energies (>81 keV). Experimental results showed that the amounts of the relaxed circular supercoiled DNA (scDNA) for gold nanoparticle-bound scDNA were more than doubled compared to that for free scDNA under otherwise identical radiation conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 18 publications
5
56
1
Order By: Relevance
“…These latter carry most of the energy of the initial fast particle [17] and can induce DNA strand breaks very efficiently even below 15 eV [18]. All these electrons can interact with water to produce radicals -in other words, GNP can be seen as an additional HO • source, as underlined by Carter et al [14] -but they can also cause direct damage as proposed by Foley et al and Zheng et al [13,16]. Here also, comparing all these results is difficult because different systems were irradiated with particles of different sizes, different coatings and at different energies, so the impact of specific characteristics such as GNP coating or size cannot be extracted from them.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…These latter carry most of the energy of the initial fast particle [17] and can induce DNA strand breaks very efficiently even below 15 eV [18]. All these electrons can interact with water to produce radicals -in other words, GNP can be seen as an additional HO • source, as underlined by Carter et al [14] -but they can also cause direct damage as proposed by Foley et al and Zheng et al [13,16]. Here also, comparing all these results is difficult because different systems were irradiated with particles of different sizes, different coatings and at different energies, so the impact of specific characteristics such as GNP coating or size cannot be extracted from them.…”
Section: Introductionmentioning
confidence: 93%
“…For the 1:1 ratio, it raises up to 3.3 which means that in the presence of GNP, only 30% of the dose is necessary to induce an equivalent damage. For DNA films bombarded with 60 keV electrons, Zheng et al obtained an EF for SC loss of 1.5 when DNA:GNP ratio was 1:1 [16] and Foley et al reported a maximum enhancement of ∼2 for a 1:100 ratio [13]. Besides, a two-fold enhancement is unanimously reported in theoretical works using conventional orthovoltage sources and a tissue loading of 0.5-1% by weight [35].…”
Section: Influence Of Dna:gnp Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…However, NIR penetration of greater than one centimeter is not practical, hence treatment is limited to tumors near the body surface or to locations accessible by NIR-emitting probes. Besides using gold nanoparticles to generate heat, Foley and coworkers have forwarded a method of using gold nanoparticles as x-ray sensitizers [Foley et al, 2005].…”
Section: Dendrimersmentioning
confidence: 99%
“…[1][2][3] The most common way to achieve enhancement is to employ gold or other high-Z X-ray absorbing nanomaterials to increase the effect of X-rays such as damage to biological targets. The enhancement was originally thought to be caused solely by the increased absorption of X-rays from the added nanomaterials, leading to generation of more electrons, radicals and other species that result in the increase of the yield of a probe reaction, which can be DNA strand breaks or hydroxylation of organic molecules.…”
Section: Introductionmentioning
confidence: 99%